Is Land Titling in Sub-Saharan Africa Cost-Effective? - Jacoby, Hanan G. (World Bank, 2012)
Is Land Titling in Sub-Saharan Africa Cost-Effective? A cost benefit analysis suggests that the current system of formal titling should not be extended in rural Madagascar and that any new system of land registration would have to be quite inexpensive to be worthwhile. Indeed, establishing a modern property rights system without legally recognizing informal rights may expand the scope for rent-seeking, thus creating additional insecurity (Atwood 1990). Purchasing a titled plot without easily being able to update the name on the document exposes the buyer to the risk that a relative of the seller, sharing the family name, might subsequently claim the plot or challenge the transfer. Analyses omitted here for brevity indicate that there is no significant advantage to owning titled land in terms of a household's access to formal credit, after controlling for the household's landholdings within the mailles (such land being much more likely to be titled), and titled plots are no more likely to be used as collateral for formal loans than are untitled plots of equivalent size, after also controlling for their position in the mailles (see Jacoby and Minten 2006). At any rate, this impact, at about 7 percent, is not large (the ceteris paribus productivity effect of having a plot in the mailles, by comparison, is on the order of 30 percent), and as argued earlier should be viewed as an upper bound on the true effect. The value of land incorporates any productivity effect of titling operating through increased land-specific investment, as well as the direct effect of expropriation risk operating through the risk-adjusted discount rate, r u. Finally, market values should also reflect the extent to which titled land is easier (or more difficult) to transact. If reported plot values reflect their true market valuation and all relevant plot characteristics can be controlled for, then OLS should produce unbiased estimates of the titling effect. The findings of this study are based on a very large sample of plots and support the notion that indigenous tenure provides adequate security for farmers to undertake the limited range of investment activities commensurate with the prevailing agricultural technology. Given this potential cost, future research should strive to determine whether such negative titling externalities are indeed empirically important.